Imagological Discourse in Modern Anthropological Reflection - Yantsos, Nataliia (Journal of Danubian Studies and Research, 2023)
The article presents the main stages in the development of imagology as a young science, and the dynamics of its evolution by Jean-Marie Carré and Marius François Guillard, who are considered pioneers in this direction. The review includes studies by contemporary Ukrainian scholars Dmytro Nalyvayko and Mykola Ilnytsky. The categorical apparatus of imagology as a branch of comparative literature, the subject of which are images of other countries and foreigners, reproduced in a particular national literature, the following concepts are noted: non-national and ino-cultural, ethno-cultural identity, self-determination, mutual perception, ethno-national stereotype, autostereotype, idea of the image of “one’s own” and “other” cultural space, etc.